Cryptococcus Neoformans: The First Reported Case of Isolation in Pigeon Excreta in the City of Votuporanga-São Paulo (Revista Brasileira Multidisciplinar, 2009)
Cryptococcocus neoformans and Cryptococcus gattii are closely related pathogenic fungi that cause pneumonia and meningitis in both immunocompromised and immunocompetent hosts. Both species are found in the environment, and are acquired via inhalation, leading to an initial pulmonary infection. We evaluated 48 air samples and 32 samples of pigeon excreta from June to August, 2007. The presence of capsule was examined with Indian ink preparation. They were also tested for urease and phenoloxidase enzymes. Cryptococcus neoformans was recovered from pigeon excreta in 3.1%. The results suggest that climatic conditions can affect the occurrence of the yeast in different environmental sources.
Keywords: Excreta; Air; Cryptococcus neoformans; Votuporanga.